Pleiotropic Menaquinone-Deficient Mutant of Bacillus subtilis - Farrand, S. K. (1973)
A multiple aromatic amino acid auxotroph of Bacillus subtilis 168 has been isolated which is unable to synthesize menaquinone-7 (MK-7) unless supplied with shikimic acid (SHK). The mutant, RB163, was isolated by selecting for resistance to low levels (1.5 μg/ml) of kanamycin. Enzymatic and genetic analyses show that the strain is an aroD mutant lacking 5-dehydroshikimate reductase. Under growth conditions in which its MK-7 deficiency is expressed, RB163 is deficient in cytochromes a, b, and c, exhibits low growth yields, and does not sporulate. Genetic analysis indicates that this pleiotropic phenotype is the result of a single genetic event. All phenotypic characteristics are reversible when the mutant is grown under conditions such that MK is synthesized. Comparison of strain RB163 with other aro mutants blocked before SHK (“early-aro” mutants) reveals interesting differences. Most early-aro mutants are cytochrome- and MK-sufficient, sporogenous, and sensitive to kanamycin when grown in the absence of SHK. However, in addition to strain RB163, two other aro mutants were found to show the pleiotropic phenotype. These three mutants have in common, and differ from other early-aro strains in, the inability to synthesize MK. It is suggested that the phenotypically wild-type aro mutants are bradytrophic, allowing enough substrate flow through the common aromatic pathway to satisfy the MK requirement. The pleiotropic mutants are thought to be completely blocked in the common pathway, thus accounting for their inability to synthesize MK.